PROBLEMATIKA ADZAN DI KOTA GORONTALO (Menelusuri Paradigma Masyarakat tentang Adzan dan Iqamat Magrib Tanpa Jeda) - Kasim, Dulsukmi (IAIN Sultan Amai Gorontalo, 2015)
Athan and Iqama are including one tawqifi issues in Islamic jurisprudence, but its application in the middle of the race still leaves the problem, particularly in the Gorontalo city. This study discusses the paradigm of Gorontalo City community about Athan and Iqama on Magrib (sunset) without pause. This research is a qualitative descriptive study with using philosophical and sociology approachs. The research data were collected through observation, interviews and documentation, then there are analyzed descriptively qualitative. The results showed that historically, the emergence of the call to prayer (Athan) and Iqama on Magrib (sunset) without a break in Gorontalo are inseparable: the history of the mosques first in Gorontalo and the presence of three figures charismatic clerics in Gorontalo city and they serves as a role model race, so that has implications for understanding Athan and Iqama on Magrib (sunset) without pause. When this phenomenon in terms of a philosophical religion, then its not found any of the arguments of the Quran and Hadis to confirms it.